GAME-BASED TECHNOLOGIES FOR TEACHING THE RUSSIAN LANGUAGE BASED ON ORAL FOLK ART - Mehriniso Tairovna Razakova (International Journal of Literature and Language Studies, 2026)
The article examines the possibilities of using game-based technologies grounded in oral folk art in the process of teaching the Russian language to students of national groups. The role of folklore as an effective means of developing communicative competence, speech activity, and students’ cognitive interest is analyzed. Special attention is paid to the use of proverbs, riddles, tongue twisters, fairy tales, folk songs, and game elements in the system of teaching the Russian language. Examples of didactic games and methodological techniques aimed at developing oral speech, expanding vocabulary, and increasing students’ motivation are presented. It is concluded that game-based technologies founded on oral folk art contribute to the creation of a favorable language environment and improve the effectiveness of teaching.